Polymers as advanced antibacterial and antibiofilm agents for direct and combination therapies. Issue 2 (20th December 2021) - Si, Zhangyong; Zheng, Wenbin; Prananty, Dicky; Li, Jianghua; Koh, Chong Hui; Kang, En-Tang; Pethe, Kevin; Chan-Park, Mary B.
Abstract : This review surveys the structure–activity of advanced antimicrobial cationic polymers with low toxicity and high selectivity. Their uses as potentiating adjuvants and as antibiofilm agents are also covered. Abstract : The growing prevalence of antimicrobial drug resistance in pathogenic bacteria is a critical threat to global health. Conventional antibiotics still play a crucial role in treating bacterial infections, but the emergence and spread of antibiotic-resistant micro-organisms are rapidly eroding their usefulness. Cationic polymers, which target bacterial membranes, are thought to be the last frontier in antibacterial development. This class of molecules possesses several advantages including a low propensity for emergence of resistance and rapid bactericidal effect. This review surveys the structure–activity of advanced antimicrobial cationic polymers, including poly(α-amino acids), β-peptides, polycarbonates, star polymers and main-chain cationic polymers, with low toxicity and high selectivity to potentially become useful for real applications. Their uses as potentiating adjuvants to overcome bacterial membrane-related resistance mechanisms and as antibiofilm agents are also covered. The review is intended to provide valuable information for design and development of cationic polymers as antimicrobial and antibiofilm agents for translational applications.